Risk management as a basis for assessing the effectiveness of the implementation of international innovation projects - Iu. V. Kuzminykh (Путеводитель предпринимателя)
This article defines a methodology for managing and accessing risks, and proposes a method for improving the risk management system. Also examines the specifics of implementing innovative projects in international activities. The features of the investment climate of countries are determined. The necessity of forming or optimizing the company’s risk management system has been proven. The main methods of risk management are presented.